Peran Mediasi Peningkatan Kunjungan dalam Hubungan antara Daya Tarik Ruang Publik Pamulang dan Permintaan Produk Makanan dan Minuman - Rianto, Rianto; Pusparani, Pusparani; Herienda, Florensia; Pradhipta, RMW Agie; Hidayat, Candra (Jurnal Ilmiah Pariwisata, 2026)
This study aims to examine the effect of tourist attractions on the increase in visits and demand for food and beverage products at Pamulang Public Space, using path analysis in a quantitative approach. The background of this research is the high potential of Pamulang Public Space as a tourist destination, followed by the increasing demand for local culinary products. The population of the study consists of visitors to Pamulang Public Space, with a sample of 100 respondents selected using an accidental sampling technique. Data was collected through Likert scale-based questionnaires and analyzed using SmartPLS. The results show that tourist attractions have a significant positive effect on increasing visits, which in turn impacts the demand for food and beverage products. The increase in visits acts as a mediator between tourist attractions and culinary product demand. In conclusion, strong tourist attractions can increase the number of visitors and contribute to the increase in demand for food and beverage products. Based on the findings, it is recommended that the Pamulang City Government improve the facilities and accessibility at Pamulang Public Space, that visitors make wise use of the facilities, and that business owners, especially Gen Z entrepreneurs, continue to innovate in offering quality culinary products while utilizing social media for promotion. Keywords: tourist attraction, visit increase, demand for food and beverage products, growth of MSMEs